Social Participation of Older Adults: A Concept Analysis - Manijeh Dehi; Farahnaz Mohammadi (Shiraz University of Medical Sciences, 2020)
Background: The concept of social participation is highly valued in old age. However, there is ambiguity and disagreement in the definition and attributes of this concept among the elderly. Purpose: This study aims to clarify and reduce the ambiguities in the concept of social participation in order to achieve a clear and understandable definition among the elderly people. Methods: For concept analysis, Walker and Avant's 8-Step method of concept analysis was used. The published papers between 2000 and 2018 were searched. 57 articles related to the concept were included in the study and accordingly, the definition, applications, attributes, antecedents, consequences and empirical referents of the concept were extracted after reviewing the resources. Results: According to the analysis, the defining attributes of the concept of elderly people's social participation included emphasis on community-based activities and interpersonal interactions, based on resource sharing, active participation and individual satisfaction. Social participation among the elderly people had individual, environmental, and social antecedents as well as individual and environmental consequences. Conclusions: The present study provided an objective and understandable picture of the concept of the elderly people's social participation. The study has pedagogical implications for promoting this concept and developing tools.